The Effect of Customer Expectations and Perceived Enjoyment on Repurchase Intention with Satisfaction as a Mediating Variable among TikTok Shop Users in the Special Region of Yogyakarta - Nugroho, Aditya; Kusuma Ningrum, Nonik; Indraswari, Nurul Myristica (Amkop Management Accounting Review (AMAR), 2025)
The development of social media has driven the transformation of online shopping behaviour, one of which is through the TikTok Shop feature that integrates entertainment content and e-commerce activities, particularly through TikTok live streaming. This study aims to analyse the influence of customer expectations and perceived enjoyment on repurchase intention, with satisfaction as a mediating variable, among TikTok Shop users in the Special Region of Yogyakarta. A quantitative method was used, with data collected through a questionnaire distributed to 154 respondents who shopped through TikTok live streaming. Data analysis was performed using with SmartPLS version 4 software. The results show that customer expectations do not have a positive and significant effect on repurchase intention. However, perceived enjoyment has a positive and significant effect on repurchase intention. In addition, this study found that satisfaction fully mediates the relationship between customer expectations and repurchase intention. Meanwhile, satisfaction also acts as a partial mediator in the effect of perceived enjoyment on repurchase intention. These findings indicate that an enjoyable shopping experience and customer satisfaction play an important role in encouraging repurchase intention on TikTok Shop.